2019
DOI: 10.1186/s12964-019-0428-1
|View full text |Cite
|
Sign up to set email alerts
|

cAMP- and cGMP-elevating agents inhibit GPIbα-mediated aggregation but not GPIbα-stimulated Syk activation in human platelets

Abstract: Background The glycoprotein (GP) Ib-IX-V complex is a unique platelet plasma membrane receptor, which is essential for platelet adhesion and thrombus formation. GPIbα, part of the GPIb-IX-V complex, has several physiological ligands such as von Willebrand factor (vWF), thrombospondin and distinct coagulation factors, which trigger platelet activation. Despite having an important role, intracellular GPIb-IX-V signaling and its regulation by other pathways are not well defined. Our aim was to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 74 publications
2
22
0
Order By: Relevance
“…There is another line of evidence for the conclusion that PKC inhibition enhances Syk and Syk substrate tyrosine phosphorylation with the possible involvement of Syk S297 phosphorylation. We recently showed that both cAMP-and cGMP-elevating platelet inhibitors (iloprost, riociguat), enhance Syk tyrosine phosphorylation/Syk activity [28]. Now, we show that iloprost (PKA pathway) strongly inhibits cvx/EB-stimulated Syk S297 phosphorylation.…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…There is another line of evidence for the conclusion that PKC inhibition enhances Syk and Syk substrate tyrosine phosphorylation with the possible involvement of Syk S297 phosphorylation. We recently showed that both cAMP-and cGMP-elevating platelet inhibitors (iloprost, riociguat), enhance Syk tyrosine phosphorylation/Syk activity [28]. Now, we show that iloprost (PKA pathway) strongly inhibits cvx/EB-stimulated Syk S297 phosphorylation.…”
mentioning
confidence: 65%
“…EB-/cvx-mediated Syk tyrosine phosphorylation is mediated by SFKs and Syk autophosphorylation [18,19,28]. Therefore, we evaluated the role of SFKs and Syk for Syk S297 phosphorylation.…”
Section: Syk S297 Phosphorylation Is Dependent On Src Family Kinases mentioning
confidence: 99%
See 3 more Smart Citations